Ionic Liquids as Antifungal Agents for Wood Preservation - Croitoru, Catalin; Roata, Ionut Claudiu (MDPI- Molecules, 2020)
Ionic liquids represent a class of highly versatile organic compounds used extensively in the last decade for lignocellulose biomass fractionation and dissolution, as well as property modifiers for wood materials. This review is dedicated to the use of ionic liquids as antifungal agents for wood preservation. Wood preservation against fungal attack represents a relatively new domain of application for ionic liquids, emerging in the late 1990s. Comparing to other application domains of ionic liquids, this particular one has been relatively little researched. Ionic liquids may be promising as wood preservatives due to their ability to swell wood, which translates into better penetration ability and fixation into the bulk of the wood material than other conventional antifungal agents, avoiding leaching over time. The antifungal character of ionic liquids depends on the nature of their alkyl-substituted cation, on the size and position of their substituents, and of their anion. It pertains to a large variety of wood-colonizing fungi, both Basidiomycetes and Fungi imperfecti.
Keywords: ionic liquids; wood; antifungal character; fungicides; preservatives; alkylimidazolium; alkylammonium